Biofilm Control With New Microparticles With Immobilized Biocide - Carla Ferreira (2013)
Biofouling of heat exchangers, pipes, and valves isan unavoidable hazard in industrial plants. Operators have to face the problems of cleaning the fouled equipment, treating the wastewater from the discharge of antimicrobial cleaning agents (biocides, surfactants, etc.), and protecting the consumer from contamination risks. To tackle these problems, a targeted cleaning technique is here proposed that unites efficient removal of the biological deposits (specifically targeting the places where deposits grow) with low consumption of cleaning agents. The goal is to develop microparticles with functionalized surfaces that act as carriers of biocidal molecules, attach to biofilm surfaces, and deliver the biocide on the desired sites. This novel biofilm control technology may provide cost-effective, environmental- and health-friendly strategies that will improve operational efficacy. Previously, our group had performed studies with polystyrene (PS) microparticles functionalized with the biocide benzyldimethyldodecylammonium chloride (BDMDAC) against biofilms of Pseudomonas fluorescens. BDMDAC-functionalized microparticles were prepared using the layer-by-layer self-assembly (LBL) technique. Since PS particles are very expensive, our group tested calcium carbonate microparticles (CaCO3) (diameter: 3m), produced by the same LBL assembly technique. These microparticles have the advantage of being cheaper, porous, and highly abundant in nature. In this study, P. fluorescens biofilms were exposed to 6.33mg/L and 11.75mg/L of BDMDAC-coated CaCO3 microparticles for 60min. This strategy promoted inactivation of 81.9% (6.33mg/L) and 93.3 % (11.75mg/L mg/L) of the total population. As a control, free BDMDAC was tested against P. fluorescens biofilms, demonstrating similar inactivation (p > 0.05) under the new strategy.